Analysis of causes of injuries among children in Daegu, Korea - Geol Ha; Man Joong Jeon; Joon Sakong (Korean Pediatric Society, 2010)
PurposeThe purpose of this study was to determine the mechanisms and exact causes of injuries to children by analyzing the medical records of children who visited emergency medical centers.MethodsWe reviewed the medical records of 7,114 pediatric patients (aged below 15 years) who visited the emergency care center (ECC) of a Yeungnam university hospital in Daegu between January 2007 and December 2009.ResultsAmong the pediatric patients who visited the ECC, 1,526 (27.2%) were admitted for injuries (boys, 979 [64.2%] and girls, 547 [35.8%]); the boy-to-girl ratio in this study population was 1.8:1. The proportion of boys was higher than that of girls over all age ranges, except for children aged less than 1 year. The highest incidence of injury due to slipping (20.5%) was noted in the 1-year-old group, and nearly half the total number of cases (49.3%) involved children who were under 4 years of age. Of the sites of injury, 999 involved the head and face (73.7%) and 134 involved the hand and wrist (9.9%). Seventy-one injuries (5.7%) occurred on the bed, 70 (5.6%) at the door, and 67 (5.3%) on the stairs. Of the approximately 250 types of injuries classified by cause, 17 accounted for 50.4% of all the injuries.ConclusionThe cause of injury could be attributed to approximately 20 causes in more than half the cases of pediatric injuries. A classification of the types of injuries and the development of appropriate preventive strategies can help avoid such injuries.